2014
DOI: 10.1590/1807-3107bor-2015.vol29.0008
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of rotatory and reciprocating movements in root canal filling material removal

Abstract: The purpose of this study was to compare the efficacy of reciprocating and rotary techniques for removing gutta-percha and sealer from root canals. Forty straight and oval single-rooted premolars were prepared up to size 30, filled with gutta-percha and sealer, and then randomly allocated to two experimental retreatment groups: ProTaper Retreatment System (PTRS) and WaveOne System (WS). Procedural errors, time of retreatment and apically extruded material were recorded for all the roots. The roots were radiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 27 publications
(22 reference statements)
4
57
3
Order By: Relevance
“…These findings corroborate the results of a recent report comparing the efficacy of a reciprocating system (WaveOne, Dentsply-Maillefer, Ballaigues, Switzerland) and ProTaper UR in retreatment, showing similarity between these two systems 26) . Our results are in consistent with the study of Rios et al 15) who reported that the Reciproc system is as effective as ProTaper UR for the removal of root canal filling.…”
Section: Discussionsupporting
confidence: 90%
“…These findings corroborate the results of a recent report comparing the efficacy of a reciprocating system (WaveOne, Dentsply-Maillefer, Ballaigues, Switzerland) and ProTaper UR in retreatment, showing similarity between these two systems 26) . Our results are in consistent with the study of Rios et al 15) who reported that the Reciproc system is as effective as ProTaper UR for the removal of root canal filling.…”
Section: Discussionsupporting
confidence: 90%
“…NiTi instruments powered by electric motors are more efficient than manual instruments to perform filling material removal within the root canal (11,12). The use of such instruments for root canal retreatment have seen significant increase in the last few years; therefore, the authors of this study decided to compare the PTR system, which was developed exactly for this purpose, and the RS, a system that has an innovative motion kinematics and has been developed for root canal preparation (5)(6)(7)(8). Several studies have evaluated the effectiveness of reciprocating systems to perform gutta-percha and root canal sealer removal; however, the benefits of their association with PUI must be evaluated (6, 7).…”
Section: Discussionmentioning
confidence: 99%
“…The complete removal of filling material from apical thirds is clinically relevant as endodontic treatment failures are usually related to bacterial remnants at the apical portion of root canals (CROZETA et al, 2016). The presence of remaining filling material in this region must be avoided when performing retreatments since the success of the endodontic intervention will depend on appropriate cleaning of this area will be impossible (SILVA et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Different techniques have been used to remove filling material in endodontic retreatments, including the use of manual files BLUHM, 2004), heated instruments (ZMENER, PAMEIJER;BANEGAS, 2006), ultrasonic devices (PIRANI et al, 2009), rotary files (IMURA et al, 2000;HAMMAD, QUALTROUGH, SILIKAS, 2008;RÖDIG et al, 2012), reciprocating files (SILVA et al, 2015;CROZETA et al, 2016), adaptive motion systems (CROZETA et al, 2016), and specific systems developed for retreatment (GU et al, 2008;TAKAHASHI et al, 2009). Several studies used distinct methods such as bidimensional radiographic analysis or destructive approaches sectioning specimens to evaluate the remaining filling after endodontic retreatment (BARRIESHI-NUSAR, 2002;CUNHA et al, 2007;BARLETTA et al, 2008).…”
Section: Introductionmentioning
confidence: 99%